APPRAISAL OF INTERNET SERVICES USAGE BY SECONDARY SCHOOL TEACHERS FOR PROFESSIONAL DEVELOPMENT IN LAGOS, NIGERIA - Semiu Olawale Makinde; Hameed Olalekan Bolaji (Sanata Dharma University Yogyakarta, 2019)
The study investigated the impact of internet services availability, accessibility and usage on secondary school teachers’ professional development in Lagos, Nigeria. Before internet services can be useful, it must be available and easily accessible. The study adopted a descriptive design survey type. The researchers’ made instrument tagged Internet Services and Professional Development Questionnaire (ISPDQ) was used to collate data. The instrument reliability coefficient was 0.79. 200 teachers were randomly sampled out of a population of 1,009 for the study from an educational district in Lagos state, Nigeria.188 questionnaires were properly filled and returned out of 200 administered which gave a response rate of 94%. Tables, charts, and percentages were used to answer the research questions. The outcome of the study shown that the available internet services in secondary schools are inadequate. The accessibility and usage of internet is a matter of concern. Hence, it was recommended among others that the public and private schools’ owners should as a matter of necessity avail teachers in the schools with internet services and sponsors them on training and retraining programmes to enhance their professional development.